Analysis of COVID-19 mortality in Colombia: Measures of disease occurrence - Bravo, Luis Eduardo; Grillo-Ardila, Elvia Karina (Universidad y Salud, 2020)
Introduction: The risk of dying from COVID-19 varies considerably between regions and countries and it is assessed through fatality indices and mortality rates. Objective: To describe the measures of mortality occurrence due to COVID-19 in Colombia. Materials and methods: Cases of coronavirus infections reported to the National Institute of Health of Colombia during the months of March and October 2020 were included. The fatality indices and mortality rates are presented as proportions and million/people ratios, respectively. Results: The fatality index for confirmed COVID-19 cases varied between regions, changed as the pandemic progressed and was initially high because diagnostic tests were conducted on severe symptomatic cases. Also, this index was underestimated due to delays in notification. In Bogota, Cali, Medellin and Cartagena, the impact of the pandemic was minor, with gradual increases and decreases in the mortality rates. On the contrary, in Barranquilla, Bucaramanga and Pasto, the curves showed sudden increments and declines, which were related to more deaths registered during the peak of the pandemic. Conclusions: The fatality indices and mortality rates of COVID-19 facilitate the monitoring of the pandemic, but they can be distorted by posthumous diagnosis of SARS-CoV-2 infection and delays in notification.